Hadoop MapReduce v2 cookbook : explore the Hadoop MapReduce v2 ecosystem to gain insights from very large datasets /: explore the Hadoop MapReduce v2 ecosystem to gain insights from very large datasets. (2015) - Gunarathne, Thilina
No abstract available